KONTRIBUSI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA DAN PROFESIONALISME GURU DI MAN KOTA PALU (Studi Kasus di MAN I dan MAN 2 Palu) - Rizka Fadliah Nur (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2020)
The researcher focused on three issues, namely: the principal's contribution to improving the performance andprofessionalism of teachers in MAN 1 and MAN 2 Palu, the strategies used by principals MAN 1 and MAN 2 Palu inimproving teacher performance and professionalism and the impact of the principal's strategy on improve teacherperformance and professionalism in MAN 1 and MAN 2 Palu. Researchers are trying to present the existence of acentral figure namely: the principal, who is considered to have contributed to improving teacher performance andprofessionalism in MAN I and MAN 2 Palu. This study used a qualitative approach with case study design. Datacollection is done by observation, interview, and documentation techniques. While data analysis techniques, researchersuse data reduction, data presentation and verification. To check the validity of the data is done with credibility,transferability, dependability, confirmability, using various sources, theories and methods so that objective data areobtained. Research informants, namely: the principal, curriculum waka, and five teachers from each school.The results showed that: (1) The principal's contribution in improving the performance and professionalism of teachersin MAN I and MAN 2 Palu were: a) The principal as a supervisor, b) As an evaluator, c) As an educator. (2) Principals'strategies in improving teacher performance and professionalism in MAN I and MAN 2 Palu are: a) Awaken theperformance of teachers by fostering a sense of belonging to the institution, b) Collaboration with other institutions inattending workshops and training, c ) Increase the teacher's task, d) Motivate, e) Conduct persuasive communication, g)Give orders in accordance with the duties and functions, h) accept suggestions and create group discipline. (3) Theimpact of the principal's strategy on improving teacher performance and professionalism at MAN I and MAN 2 Paluare: a) Teachers always make learning plans, b) Teachers use varied learning methods, c) Teachers create a conduciveclassroom climate, d) The teacher is able to use learning media that can attract student learning interest.